Survey and construction of prediction model of HPV infection in the genital tract of women undergoing health checkups in Chengdu - TANG Yijiao; ZENG Deling; TAN Song3; TIAN Li; DENG Yuyan (Yixue xinzhi zazhi)
Objective To investigate and establish a prediction model of HPV infection in the genital tract of women undergoing health checkups in Chengdu.Methods Women who underwent occupational physical examination in three hospitals in Chengdu from March 2022 to March 2023 were selected as study subjects. The possible factors associated with genital tract HPV infection were collected. The study subjects were divided into the model group and validation group in a 7∶3 ratio, and divided into an infected group and a non-infected group according to the presence or absence of HPV infection. LASSO regression was used to screen the potential factors of HPV infection. Logistic regression model was used to establish a risk prediction model for the risk of HPV infection and to draw a nomogram graph The receiver operating characteristic (ROC) curve, area under curve (AUC), calibration curve and decision curve were used to assess the discrimination, calibration and clinical applicability of the risk prediction model.Results A total of 2,318 women undergoing health checkups were included and 481 (20.75%) were infected with HPV, of which 316 (65.70%) were single infections, 165 (34.30%) were multiple infections. 1,622 cases in the model group and 696 cases in the validation group. 341 cases were in the infected group and 1,281 cases were in the non-infected group in the model group. The LASSO and Logistic regression results showed that age [OR=0.955, 95%CI(0.912, 0.999)], number of births [OR=4.392, 95%CI(1.420, 13.583)], age at first sexual intercourse [OR=0.870, 95%CI(0.774, 0.979)], condom use [OR=0.314, 95%CI (0.109, 0.905)], number of sexual partners [OR=6.068, 95%CI(1.825, 20.177)], circumcision of sexual partners [OR=3.218, 95%CI(1.042, 9.936)], prevalence of sexually transmitted diseases [OR=3.476, 95%CI(1.071, 11.277)], inflammation of the genital tract [OR=3.526, 95%CI(1.185, 10.494)], and cervical columnar epithelial ectasia [OR=4.375, 95%CI(1.374, 13.934)] were the independent correlates of HPV infection in health checkup’s women (P0.05). The results of calibration curves showed that the prediction curves in the model group and validation group basically fitted the standard curve. The decision curve showed that when the risk probability thresholds of the model and validation groups were 0.05~0.90 and 0.05~0.78, respectively, the patient benefit was greater than 0.Conclusion The prevalence of HPV infection in the health checkups of women in Chengdu was 20.75%, which was mainly affected by age, number of births, age at first sexual intercourse, condom use, number of sexual partners, circumcision of sexual partners, prevalence of sexually transmitted diseases, inflammation of the genital tract, and cervical columnar epithelial ectasia. The risk prediction model for HPV infection in the female genital tract based on the above factors is valuable for clinical use.